HUBUNGAN PAPARAN KEBISINGAN TERHADAP STRES KERJA PADA PORTER GROUND HANDLING DI KOKAPURA AHMAD YANI SEMARANG - Apladika Apladika; Hanifa Maher Denny; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2016)
Noise is kind of unwanted sounds that coming from working tools which at certain level could cause physical disturbance as well as psychology. Job stress is job stressor which causing Individual reaction such as physiological, psychological, behavior reaction. Based on the result of problem identification at Kokapura Ahmad yani, it is known that 13 workers were out or turn over since March until May 2016 which considered as many. the amount of responsibility that carry by porter on handling passenger’s baggage every day and the amount of noise that considered beyond the limit that assign by regulation are two things that quite possibly causing stress in ground handling porter. The purpose of this research is to analyze the connection between noise and stress job in ground handling porter at Kokapura Ahmad Yani Semarang. Type of research that use is explanatory with cross sectional as it approach. The amount of population in this research is 49 peoples. The amount of sample that uses is 41 peoples. Based on statistical test that uses rank spearman test, it is obtain p value as much as 0,035 which shown there is connection between noise and job stress. Researcher advising the company to socialize working guide that safer for porter, and also preparing PPE that appropriate to handle noises and do working time rotation between porter and make up porter.